(untitled) (Eurasian Journal of Philology Science and Education, 2018)
The article is devoted to the ontology of scientific-technical terminology and its codification in the lexicographical words and aimed at defining key concepts terminology and codification as nature of the term. The key categories of modern terminology are established, the scientific definition of the word-term, terminology as a system is given. When determining the nature of the scientific and technical term, the place and its functional significance are determined in the general system of the vocabulary of any language. The article also explores the semantic structure of the scientific – technical term and reflects in it the latest achievements of science and technology of our days. No coincidence that the number of new terms exceeds the number of neutral common vocabulary. The article also gives description complex of the syntactic functions of the word-term, its properties compatibility. All this is within the competence of the lexicographical codification of the language. are considered The scientific and technical terms of the electric power industry , which reflect the possibility of combining words in speech activity, and they are much broader than the combinations offered by dictionaries. It is argued that an understanding of the linguistic compatibility of terms helps in the correct use of the concept in speech